Compaction effects on permeability of spherical packing. Issue 9 (6th May 2020) - Zhang, Duzhou; Tian, Zhiguo; Chen, Zhiqiang; Wu, Dengyun; Zhou, Gang; Zhang, Shaohua; Wang, Moran
Abstract : Purpose: The purpose of this paper is to investigate the evolution of the permeability of spherical packing during cold compaction by pore-scale modeling. Design/methodology/approach: The discrete element method (DEM) is used to generate spherical packing structure under different compressive pressures and the Lattice Boltzmann method (LBM) is adopted to calculate the permeability of each spherical assembly. Findings: It is found that the decrease of the porosity is the main reason of the reduction in permeability in the initial compression stage, but its influence becomes insufficient in the late compression stages. Besides, two empirical formulas are obtained, which describe the relation between the permeability and the equivalent mean diameter and the variation of normalized permeability with compressive pressure, respectively. Research limitations/implications: In this study, the authors study the spherical particles and ignore the non-spherical effects. Besides, the classical contact model, the linear-spring-damping model, is used in DEM, so the plastic deformation cannot be considered. Originality/value: The DEM and the LBM are well combined to study the compaction effects on permeability of spherical packing. Two simple expressions of the spherical packing structure with uniform diameter distribution are given for the first time.